The Civic Cults of Local Reformist Bishops in Dalmatia: Success and Failure - Marinković, Ana (Array, 2011)
The bodies of John of Trogir, Rainer of Split, and Gaudence of Osor, Dalmatian bishops of the 11th- 12th centuries, remained (or were regained) and were venerated in the cities where they had exercised their episcopal office. Each of the bishops engaged in defending interests of the local Church and/or the civic community, they nurtured tight bonds with local Benedictine communities, and died in the odour of sanctity. The paper is analysing the circumstances which lead to their success or failure as the major civic patron ; primarily the existence of another strong local cult, but also the need of reintroducing reformist or other protective measures in the later medieval period (notably facing heretical movement), as well as the particular circumstances of local communal developments. The issue of the means of cult promotion is also touched upon: implementing the elements of „civic quality“ in the Vitae (notably the episodes related to the relics' local miracle working), documenting the miracles at the tomb, commissioning ever new reliquaries for the body part relics of the saints, building new housing for the relics, etc. Scrutinizing the Statute Laws and other ordinances concerning the public feasts and related obligations of the secular authorities is throwing light on the question of who was supporting and directing the success (and failure) of the cult: Benedictine communities, cathedral chapters, or rather fraternities and various levels of government (local/Hungarian/Venetian).